P61 Implementing transition to adult services in a district general hospital in the UK. (18th November 2019) - Adodra, A; Trivedi, A; Barbour, L; Ganapathi, J; Sheppard, C
Abstract : Introduction: The NHS has well developed adult and paediatric services. However Young People (YP) aged 16-25 years often fall between these services due to inadequate healthcare provision, resulting in adverse health outcomes. Transition to Adult Services (TAS) is already well developed in many tertiary paediatric centres, beginning as early as 11 years of age. This allows YP to be empowered and to gain familiarity with adult services. However, non-specialist TAS is yet to be established at District General Hospital (DGH) level. The aim of this Quality Improvement Project (QIP) was to develop and implement a non-specialist and developmentally appropriate TAS in a busy DGH in London. Method: NICE guidelines for TAS highlighted that a stepped approach can support the implementation of successful TAS care pathways. Over a period of 14 months, all relevant stakeholders were identified resulting in the formation of a multidisciplinary Clinical Working Group for TAS. This enabled a scoping exercise to be undertaken combined with a gap anaylsis as well as both operational and strategic reviews of the local TAS. Results: To date, the achievements of the QIP include: Identifying YP needing TAS – from acute admissions, outpatients and in the community Empowering YP – through the use of a validated survey for Medicines Transition Engaging the multidisciplinary team: acute paediatric service, paediatric community service, adult emergency care as well as adult and paediatric clincial nurse specialists Implementation of a flag identfier when YP in Transition present to the Emergency Department Appointment of a pilot Transition Nurse – CCG funding approved. A patient–facing Medicines Transition Pilot, results of which won the patient voted First Prize at the Trust Quality Improvment Awards Bespoke TAS Emergency Care plan for each YP on Transition Pathway – ongoing process Conclusion and next steps: The following actions are in process: Patient passport combining YP feedback with their medical needs Formalising referral pathways to adult services Improving confidence of YP for TAS by collating, standardising and disseminating information relevant for this group. Establishing Joint Paediatric and Adult Transition clinics YP settling into adult services – via follow–up questionnaire/service We would also like to acknowledge the support of the remainder of the Clinical Working Group at The Hillingdon Hospital, who gave so generously of their time, energy, ideas, solutions and enthusiasm. Each individual's contribution moved us closer to our goal.